Analisis Kepuasan Konsumen terhadap Kualitas Produk dan Pelayanan di Voltvet Eatery and Coffee menggunakan Metode Customer Satisfaction Index (CSI) - Pranata, Made Nanda; Hartiati, Amna; Sadyasmara, Cokorda Anom Bayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
The purpose of this research is to: (1) find out the attribute of products and services that are considered important by customers to achieve customer satisfaction of the quality products and service. (2) determine the level of customer satisfaction with the quality of products and services. (3) Determine attributes that need to get a priority in quality improvement of products and services to enhance customers satisfaction at Voltvet Eatery and Coffee . This research uses the methods of Customer Satisfaction Index (CSI) and the Potential Gains In Customer Values (PGCV) that includes quality products including food, beverage , coffee, pric e and promotion, while the quality of service including physical evidence, reliability, responsiveness, assurance, and empathy, respondents used amounted to 94. The data obtained were analyzed using SPSS 25.0 applications and microsoft excel. The Result of the research showed that all of the product and service quality attribute are considered important by customers . The level of customer satisfaction based on the CSI to quality product is 8 2,85 % and on services 8 3,83%, which shows that customers very satisfied with product and service at Voltvet Eatery and Coffee . Quality attribute product that needs attention is the presentation with a PGCV index value 4.017; discount with the value of the index PGCV 3.891; and the consistency of food per serving with the value of the index PGCV 3.838;   while services quality attribute that need to gain priority are availability of parking lots with the value of the index PGCV 4.200 ; wifi facilities with the value of the index PGCV 3.636, and employee appearance with indeks of PGCV 3. 121. Keywords : product quality, service quality, Customer Satisfaction Index (CSI), Potential Gain In Customer Values (PGCV) .